Critical approaches in leadership education: Making the case for racial equity via institutional type. Issue 171 (18th October 2021) - Collins, Jasmine D.; Whitney, Rich
Abstract: In this introductory article, we offer a theoretical overview of racial equity and provide the rationale for pursuing an issue related to racial equity in leadership education. We also make the case for examining marginalized institutional contexts as a step toward advancing racial equity in postsecondary leadership education.